Programma: 18,25 november, 2,9,16 december Showcase; 21 november Det-ri-mental; 28 november Billy Cobham; 30 november Kreator, Grip Inc., Hatesquad
Programma: 18,25 november, 2,9,16 december Showcase; 21 november Det-ri-mental; 28 november Billy Cobham; 30 november Kreator, Grip Inc., Hatesquad.